Firm characteristics and credit accessibility of micro and small enterprises in Meru town-Kenya - Kobia Faith Kathure (Meru: Meru University of Science and Technology, 2022)
Micro and small enterprises have been known to be drivers of social economic department. Despite the effort of the government in formulating and implementing policies intended to enhance entrepreneurship, several challenges are still being experienced by entrepreneurs with the major ones being the requirements of lenders of different financial institutions. This research aimed to assess firm characteristics and credit accessibility of micro and small enterprises in Meru Town. The biggest challenge is that few MSE owners are fully aware of the traits that lenders look for when approving credit. The goal of the study was to look into the influence of firm size, profitability, firm assets and business ownership on credit availability for micro and small businesses. To support the study, the trade-off Theory, pecking order Theory, and imperfect Information Theory underpinned the study. The study employed the use of a questionnaire as the primary method of data collection. A target population of 800 registered MSEs was used for stratified sampling, yielding a sample size of 89 respondents, all of whom were owners or managers of these enterprises. The data was analyzed using descriptive statistics and a multiple linear regression model. The research established that, obtaining business finance from various financial organizations is one of the most difficult challenges that entrepreneurs in modern economics confront. The study uncovered that the variables; firm size, firm assets, profitability and business ownership significantly influenced credit accessibility of MSEs. In general, the study findings of regression analysis revealed a significant relationship between the firm characteristics and credit accessibility (r-0.89). The study would make a significant contribution to the current body of knowledge, particularly for academicians that may use it to advance their research in this field by analyzing the literature and identifying gaps. Based on the study findings, this research recommends for further investigations of other variables affecting credit accessibility of MSEs.